IoT-based Low-cost Children Tracker System - Marhoon, Hamzah M; Ma'arif, Alfian; Aljanabi, Haider Dheyaa Kamil; Alanssari, Ali Ihsan; Nadheer, Israa (Signal and Image Processing Letters, 2023)
Recently many cases of missing children between ages 14 and 17 years have been reported. Parents always worry about the possibility of kidnapping their children. This work proposes an Android-based solution to aid parents to track their children in real-time. Nowadays, most mobile phones are equipped with internet service capabilities allowing them to connect with the world. The system's architecture is built on two main components: GPS satellite and IoT technology. The most important features of this work are the low cost, lightweight, and small size. The Blynk app is installed on the mobile phone and the GPS is attached to the NodeMCU microcontroller. The location information is reached through the Blynk app with the help of map services.